2019
DOI: 10.9745/ghsp-d-18-00265
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Scale of the Saving Mothers, Giving Life Approach in Uganda and Zambia

Abstract: The Saving Mothers, Giving Life district health systems strengthening approach provides a sustainable model for reducing maternal mortality at scale. Lessons from the learning districts demonstrated increased efficiency in allocation of resources for maternal and newborn health, better use of strategic information, improved management capacities, and increased community engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…When donor funding recently decreased for blood-safety programs, the government of Zambia increased its health budget to ensure an adequate supply of blood for its citizens. (See the article by Healey et al from the SMGL supplement 71 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When donor funding recently decreased for blood-safety programs, the government of Zambia increased its health budget to ensure an adequate supply of blood for its citizens. (See the article by Healey et al from the SMGL supplement 71 …”
Section: Discussionmentioning
confidence: 99%
“…Between these initiatives, over half of the Ugandan population will be covered by a district health systems strengthening approach by 2020. (See the articles by Healey et al 71 and Palaia et al 73 from the SMGL supplement. )…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the Ugandan MOH's budget has been reduced in the past year. (For additional analysis and discussion on SMGL sustainability, see the companion article by Healey and colleagues 29 in this supplement. )…”
Section: Discussionmentioning
confidence: 99%
“…12 For example, an evaluation of the large-scale, comprehensive Saving Mothers Giving Life initiative, which aimed to rapidly reduce maternal mortality in Zambia and Uganda from 2012 to 2016 through community health worker mobilization, doctor and nurse training, and facility upgrades, 13 found that the intervention's ability to foster a sense of local ownership around the intervention was an essential factor in the early maintenance of its gains in maternal and child health outcomes. 14 The 2005 Paris Declaration on Aid Effectiveness and the 2008 Accra Agenda for Action both argue in favor of a country defining its own development priorities and designing and leading programs promoting these priorities. 15 The need for country or community ownership of health interventions, for example through sustained government or ministry of health funding or community contributions, is rooted in ideological values of self-determination and has been posited to be an effective approach to sustainability.…”
Section: Introductionmentioning
confidence: 99%
“… 12 For example, an evaluation of the large-scale, comprehensive Saving Mothers Giving Life initiative, which aimed to rapidly reduce maternal mortality in Zambia and Uganda from 2012 to 2016 through community health worker mobilization, doctor and nurse training, and facility upgrades, 13 found that the intervention’s ability to foster a sense of local ownership around the intervention was an essential factor in the early maintenance of its gains in maternal and child health outcomes. 14 …”
Section: Introductionmentioning
confidence: 99%